Understanding Customer Loyalty Behavior in Islamic Microfinance: Examining the Role of Proactive Service (Jemput Bola) and Customer Trust - Mohamad Mondir; M. Ilham Zainullah; Haqiqotus Sa’adah (LP2M Universitas Ibrahimy, 2026)
This study explores how proactive service (jemput bola) influences customer loyalty in Islamic microfinance institutions, particularly at BMT NU East Java, and examines the role of customer trust in this relationship. The research is motivated by the growing shift toward digital financial services, raising questions about whether direct, face-to-face service approaches remain effective. Using a quantitative method, data were collected from 70 customers through purposive sampling and analyzed using SEM-PLS. The findings show that proactive service has a strong and significant impact on customer loyalty. Customer trust also plays an important role in strengthening loyalty. However, it was found that trust does not act as a moderating variable in the relationship between proactive service and customer loyalty. This indicates that customers tend to respond directly to the quality of service they receive, without necessarily relying on trust as an intermediary factor. Overall, the study highlights that the jemput bola strategy remains relevant and valuable, especially in building close relationships with customers, even in the midst of increasing digitalization in the financial sector.